Analisis hasil uji kompetensi guru matematika sekolah menengah pertama (SMP) di Kota Tasikmalaya - Redi Hermanto; Satya Santika (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
Certification of teachers that has lasted more than a decade aimed to produce professional teachers, thus impacting significantly to the advancement of education in Indonesia. But the reality in Tasikmalaya, West Java, it is very much different from the expectations. The majority of teachers are even more concerned about the increase of social status than the professional quality as an educator. More recently the government has implemented Teacher Competency Test (UKG), which was held simultaneously throughout Indonesia with the aim to determine the ability of teachers’ pedagogical and professional competencies. The purpose of this study was to determine the mapping of the teachers’ competency by rank, domain competence, academic qualification, age, gender, and see the difference in results UKG based certification status. Outputs resulting from this study were (1) to map the results UKG mathematics of junior high school in Tasikmalaya, (2) to formulate recommendations or proposals regarding the improvement of the UKG (3) to formulate recommendations or proposals of the sustainable planning of professional development for teachers. The method used in this research were studied documentation, interviews and questionnaires open. The mapping of UKG results can be used as consideration in evaluating the program especially in what improvements need to be prioritised. By using the techniques of interviews and open questionnaire, was expected collect information of the effect of UKG for the teachers.